Blue and green jets in laboratory discharges initiated by runaway electrons. (October 2015) - Beloplotov, D V; Lomaev, M I; Sorokin, D A; Tarasenko, V F
Abstract: Spectral and amplitude-temporal characteristics of plasma radiation of nanosecond pulse-periodic discharge in air, nitrogen and argon in pressure range of 30-760 Torr were investigated. Discharge gap geometry was a "point-to-plane". Voltage pulses of negative polarity (amplitude, FWHM and risetime was 13 kV, 10 ns and 4 ns, respectively) were applied to a pointed cathode made of different metals (stainless steel, aluminum and copper). Jets of different colour were observed near a cathode tip. They are formed due to explosive emission. Colour of jets depends on the cathode material. Intense lines of the atoms and ions of iron in the wavelength range of 200-600 nm, aluminum with λ = 394.4, 396.15 nm, including multiply charged ion Al VI with λ = 360.39 and 361.65 nm, copper with λ = 324.8, 327.3, 510.6, 515.3, 521.8, 522 nm were registered. The resonance energy transfer from metastable A 3 Π + u level of nitrogen molecule to 3d 10 4p level of Cu I was found. As a result a luminescence duration of Cu I was about 1.5 μs at duration of discharge current of 1.5 ps. During constriction of the diffuse discharge the sputtering of material occurs in the direction perpendicular to the longitudinal axis of the discharge gap.